Higher-order cyclization reactions of alkenyl Fischer carbene complexes: a new selective all-carbon [8 + 2] cyclization with 8-methoxyheptafulvene and computational mechanistic analysis. Issue 28 (22nd June 2016) - García-Rodríguez, Jaime; González, Jairo; Santamaría, Javier; Suárez-Sobrino, Ángel L.; Rodríguez, Miguel A.
Abstract : A new all-carbon [8 +2] cycloaddition of alkenyl Fischer carbene complexes is described. Abstract : A new higher-order cyclization reaction of alkenyl Fischer carbene complexes is described. Chromium and tungsten alkenyl Fischer carbene complexes react toward 8-methoxyheptafulvene through an all-carbon formal [8 + 2] cycloaddition reaction with complete regio- and stereoselectivity. Tetrahydroazulene compounds bearing four consecutive stereocenters are generated. The reaction mechanism is rationalized based on computational calculations. It was found that this transformation proceeds through a concerted process. The nature of the observed stereo- and regioselectivity can be attributed to both steric and electronic factors.